2010
DOI: 10.1089/thy.2009.0260
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis of the Promoter Region of Phosphodiesterase Type 8B (PDE8B) in Correlation with Inactivating PDE8B Mutation and the Serum Thyroid-Stimulating Hormone Levels

Abstract: Background: Human phosphodiesterase (PDE) type 8B (PDE8B) is located at 5q14.1 and is known as the PDE with the highest affinity to cAMP. We recently described a family with bilateral micronodular adrenocortical disease that was apparently caused by an inactivating PDE8B mutation (H305P). As a result of a genome-wide study, a strong association between six polymorphic variants in the PDE8B promoter and serum levels of the thyroid-stimulating hormone (TSH) has been recently reported. Despite an extended analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…PDE8B encodes a cyclic AMP PDE enzyme (11,25), strongly expressed in the thyroid gland (26,27,28) but undetectable in the pituitary gland, and its influence on thyroid hormone parameters should be via hydrolysis and inactivation of cAMP in the thyroid, in response to (11). Among the several mechanisms suggested to explain increased TSH levels in obesity, the most favoured one is increased leptin-mediated production of pro-TRH (3,28,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDE8B encodes a cyclic AMP PDE enzyme (11,25), strongly expressed in the thyroid gland (26,27,28) but undetectable in the pituitary gland, and its influence on thyroid hormone parameters should be via hydrolysis and inactivation of cAMP in the thyroid, in response to (11). Among the several mechanisms suggested to explain increased TSH levels in obesity, the most favoured one is increased leptin-mediated production of pro-TRH (3,28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Each copy of the minor A allele was found to be associated with an increase in TSH concentration of 0.13 mIU/l. Remarkably, this polymorphism is located in intron 1 of PDE8B, a gene that encodes a highaffinity cAMP-specific PDE expressed in the thyroid gland and, likely, regulating TSH signalling (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…PDE8A occurs in high levels in Leydig cells, where it plays an important role in luteinizing hormone (LH) control of testosterone synthesis (391). PDE8B is abundant in mouse adrenal fasciculata cells, where it modulates steroidogenesisis in response to adrenocroticotropic hormone (ACTH) (382a), and it is also implicated in regulation of thyroid-stimulating hormone (TSH) levels, in adrenocortical disease (149), and in the insulin response of pancreatic islets to glucose (98). PDE10 is abundant in certain neuronal cells and is the target of medications being developed for treatment of several neuropsychiatric disorders (243, 244, 303, 332, 346 -348, 378).…”
Section: B Diversity Of the Mammalian Phosphodiesterase Superfamilymentioning
confidence: 99%
“…Genome-wide association studies have also identified several genes involved in thyroid hormone signaling. Three SNPs at intron 1 of the phosphodiesterase 8B (PDE8B) gene are significantly associated with serum TSH levels [40,41]. PDE8B encodes a high-affinity cAMP-specific phosphodiesterase catalyzing the hydrolysis and inactivation of cAMP.…”
Section: Genetic Basis For Variationmentioning
confidence: 99%